2023
DOI: 10.1126/science.adc8810
|View full text |Cite
|
Sign up to set email alerts
|

A mesothelium divides the subarachnoid space into functional compartments

Abstract: The central nervous system is lined by meninges, classically known as dura, arachnoid, and pia mater. We show the existence of a fourth meningeal layer that compartmentalizes the subarachnoid space in the mouse and human brain, designated the subarachnoid lymphatic-like membrane (SLYM). SLYM is morpho- and immunophenotypically similar to the mesothelial membrane lining of peripheral organs and body cavities, and it encases blood vessels and harbors immune cells. Functionally, the close apposition of SLYM with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(173 citation statements)
references
References 52 publications
5
128
2
Order By: Relevance
“…Second, gadobutrol is a hydrophilic substance that does not pass the intact BBB, nor does it permeate the cell membrane or interact with other molecules of the brain. Third, the transport of plasma biomarkers and CSF tracer in the subarachnoid compartments may differ due to the membranes compartmentalizing the subarachnoid space 44 , 45 . In this regard, ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, gadobutrol is a hydrophilic substance that does not pass the intact BBB, nor does it permeate the cell membrane or interact with other molecules of the brain. Third, the transport of plasma biomarkers and CSF tracer in the subarachnoid compartments may differ due to the membranes compartmentalizing the subarachnoid space 44 , 45 . In this regard, ref.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, ref. 45 recently described a subarachnoid lymphatic-like membrane (SLYM) compartmentalizing the subarachnoid space, where this mesothelial membrane was impermeable to substances >3 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Møllgård et al found the presence of a fourth cranial meningeal layer in the mouse brain, naming it subarachnoid lymphatic-like membrane (SLYM) [ 38 ]. We did not detect such a fourth layer in the human ON specimen investigated here.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…SLIM has a structure similar to the mesothelium, is closely connected to the endothelium of cerebrovascular vessels and regulates the exchange of substances between cerebrospinal fluid and veins. It is worth noting that the number of immune cells increases in the immune activation state, suggesting that SLYM may play a role in regulating brain immune homeostasis ( Møllgård et al, 2023 ). Overall, there are still many questions about the influence of special structural and functional changes on BBB homeostasis during the perioperative period that have yet to be explained.…”
Section: Potential Pathophysiological Processes and Mechanismsmentioning
confidence: 99%